The Build-up of Auditory Stream Segregation: A Different Perspective - Deike, Susann; Heil, Peter; Böckmann-Barthel, Martin; Brechmann, André (Frontiers in Psychology, 2012)
The build-up of auditory stream segregation refers to the notion that sequences of alternating A and B sounds initially tend to be heard as a single stream, but with time appear to split into separate streams. The central assumption in the analysis of this phenomenon is that streaming sequences are perceived as one stream at the beginning by default. In the present study, we test the validity of this assumption and document its impact on the apparent build-up phenomenon. Human listeners were presented with ABAB sequences, where A and B were harmonic tone complexes of seven different fundamental frequency separations (∆f) ranging from 2 to 14 semitones. Subjects had to indicate, as promptly as possible, their initial percept of the sequences, as either “one stream” or “two streams”, and any changes thereof during the sequences. We found that subjects did not generally indicate a one-stream percept at the beginning of streaming sequences. Instead, the first perceptual decision depended on ∆f, with the probability of a one-stream percept decreasing, and that of a two-stream percept increasing, with increasing ∆f. Furthermore, subjects required some time to make and report a decision on their perceptual organization. Taking this time into account, the resulting time courses of two-stream probabilities differ markedly from those suggested by the conventional analysis. A build-up-like increase in two-stream probability was found only for the ∆f of 6 semitones. At the other ∆f conditions no or only minor increases in two-stream probability occurred. These results shed new light on the build-up of stream segregation and its possible neural correlates.